2011
DOI: 10.2147/ijn.s24073
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal myotube formation enhanced by electrospun polyurethane carbon nanotube scaffolds

Abstract: Background: This study examined the effects of electrically conductive materials made from electrospun single-or multiwalled carbon nanotubes with polyurethane to promote myoblast differentiation into myotubes in the presence and absence of electrical stimulation. Methods and results: After electrical stimulation, the number of multinucleated myotubes on the electrospun polyurethane carbon nanotube scaffolds was significantly larger than that on nonconductive electrospun polyurethane scaffolds (5% and 10% w/v … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 40 publications
1
56
0
Order By: Relevance
“…Thus, these scaffolds can be loaded with nanoparticles such as carbon nanotubes (CNT) and graphene oxide to increase electrical conductivity of the scaffolds. These particles have been shown to promote myoblast differentiation and also provide a platform which is electrically conductive [56][57][58]. Hence, upon myoblast cell seeding and adhesion, the scaffolds can be electrically stimulated [59].…”
Section: Cell Attachment and Viabilitymentioning
confidence: 99%
“…Thus, these scaffolds can be loaded with nanoparticles such as carbon nanotubes (CNT) and graphene oxide to increase electrical conductivity of the scaffolds. These particles have been shown to promote myoblast differentiation and also provide a platform which is electrically conductive [56][57][58]. Hence, upon myoblast cell seeding and adhesion, the scaffolds can be electrically stimulated [59].…”
Section: Cell Attachment and Viabilitymentioning
confidence: 99%
“…Sirivisoot and Harrison (2011) reported that skeletal myotubes cultures grown on a polyurethane-CNTs composite scaffold and electrically stimulated through the scaffold itself, show a higher number and length of cells compared to cultures grown without electrical stimulation. Furthermore, in the presence of electrical stimulation, myotube formation increased in the polyurethane-CNTs composite compared to polyurethane alone.…”
Section: Cnts For Cardiac Cells Electrical Interfacingmentioning
confidence: 99%
“…For example, myoblasts increase myotube formation on electrically conductive scaffolds, even in the absence of electrical stimuli [14,15]. Extracellular cues influence myotube formation and muscle contraction on electrically conductive scaffolds in the presence of electrical stimulation [16][17][18]. Therefore, by incorporating conducting polymer nanofibres into the three-dimensional scaffolds, the electrical conduction of scaffolds may increase, while maintaining biocompatibility and supporting cell differentiation.…”
Section: Introductionmentioning
confidence: 99%